The Effect of the Implementation of Family Functions with Self-Harm Behavior in Adolescents in the Digital Age - Puji Lestari; Liyanovitasari Liyanovitasari; Rosalina Rosalina (GLOBAL HEALTH SCIENCE GROUP, 2025)
The prevalence of self-harm behavior among adolescents has increased significantly. Research conducted by Muehlenkamp et al. (2012) shows that about 17-18% of adolescents worldwide report having committed self-harm at least once in their lives. Family has a huge influence on the psychological and emotional development of adolescents. The purpose of this study is to find out how the implementation of family functions affects self-harm behavior in adolescents. This study uses a quantitative method with a cross-sectional design. The researcher will examine how to carry out family functions and also how self-harm behavior is carried out by adolescents, then look at the relationship between these two things. Research Subject: Adolescents aged 12-18 years as many as 183 students with total sampling technique. Data were collected using the Family Assessment Device (FAD) instrument to assess family function and the Deliberate Self-Harm Inventory (DSHI) to measure the frequency and intensity of self-harm in adolescents. Data will be analyzed using the Chi square correlational statistical technique to see the relationship between family function and self-harm behavior. The results showed that family function in the good category was 61.7% while family function in the bad category was 38.3%. Self-harm behavior in adolescents 23.5%. Based on the Chi Square test, a p value of 0.048 was obtained, meaning that there is a significant relationship between the implementation of family functions and self-harm behavior in adolescents.